The DNA-binding protein pUL57 of human cytomegalovirus: comparison of specific immunoglobulin M (IgM) reactivity with IgM reactivity to other major target antigens. - Maine, G T (1996)
In this work we used PCR to amplify the DNA regions coding for two polypeptides from pUL57 of human cytomegalovirus (amino acids 540 to 601 and 1144 to 1233) and showed that both portions reacted very efficiently with immunoglobulin M in sera of acutely infected subjects. However, pUL57 is not an essential antigen for the replacement of or supplement to a cocktail of recombinant protein antigens containing portions of ppUL32, -44, -83, and -80a in immunoglobulin M serology.